Inflammatory markers associated with osteoarthritis after destabilization surgery in young mice with and without Receptor for Advanced Glycation End-products (RAGE) - Larkin, D. J.; Kartchner, Jeffrey Z.; Doxey, Alexander S.; Hollis, Weston R.; Rees, Jeffrey L.; Wilhelm, Spencer K.; Draper, Christian S.; Peterson, Danielle M.; Jackson, Gregory G.; Ingersoll, Chelsey; Haynie, S. S.; Chavez, Elizabeth; et al. (Frontiers in Physiology, 2013)
HtrA1, Ddr-2 and Mmp-13 are reliable biomarkers for osteoarthritis (OA), yet the exact mechanism for the upregulation of HtrA-1 is unknown. Some have shown that chondrocyte hypertrophy is associated with early indicators of inflammation including TGF- and the Receptor for Advanced Glycation End products (RAGE). To examine the correlation of inflammation with the expression of biomarkers in osteoarthritis, we performed right knee destabilization surgery on four week old wild type and RAGE knock-out (KO) mice. We assayed for HtrA-1, TGF-1, Mmp-13, and Ddr-2 in articular cartilage at 3, 7, 14 and 28 days post-surgery by immunohistochemistry on left and right knee joints. RAGE KO and wild type mice both showed staining for key OA biomarkers. However, RAGE KO mice were significantly protected against OA compared to controls. We observed a difference in the total number of chondrocytes and percentage of chondrocytes staining positive for OA biomarkers between RAGE KO and control mice. The percentage of cells staining for OA biomarkers correlated with severity of cartilage degradation. Our results indicate that the absence of RAGE did protect against the development of advanced OA. We conclude that HtrA-1 plays a role in lowering TGF-1 expression in the process of making articular cartilage vulnerable to damage associated with OA progression.